Technical efficiency and impact of improved farm inputs adoption on the yield of haricot bean producer in Hadiya zone, SNNP region, Ethiopia - Tamirat Beyene; Wondaferahu Mulugeta; Tesfaye Merra (Cogent Economics & Finance, 2020)
Haricot bean is one of the most important food legumes of Ethiopia and it is considered as the main cash crop and the least expensive source of protein for the farmers. Low production and productivity, which are mainly associated with poor adoption and inefficient implementation of improved farm technologies, were among the major problems. Adoption and efficient utilization of improved farm inputs is one of the most promising ways to reduce food insecurity in study area. However, the adoption and implementation of these improved farm inputs is constrained by various factors. So, the aim of this study was to analyze the technical efficiency and impact of improved farm inputs adoption on the yield of haricot bean producers. A multi-stage sampling technique was employed to select 231 sample household heads and they were interviewed using structured interview schedule. Data analysis was done with the help of Stochastic Frontier Analysis; mainly Cobb-Douglas Production Function, logistic regression model were employed. The Stochastic Production Frontier result revealed that the allocated amount of land, labour, seed, chemical fertilizer and oxen were appeared to be positively and significantly influencing haricot bean production of both adopters and total sampled householders. The result of logistic regression model indicated that the probability of adoption of improved farm inputs affected by extension service, information access and cooperative membership positively and by market distance and crop diversification negatively. Therefore, specialization, asset formation, innovative institutional arrangement, information, extension and farmers training accompanied with more access to chemical fertilizer in the study area.
Keywords: 330; Adoption; Efficiency; Frontier; Impact; Smallholder farmers